Audience Expectations and Teacher Demands - Brooke, Robert, 1958- (Book collections on Project MUSE., 1989)
The audience-the community of readers who will use the texts a writer produces-must be an important influence on the writer for his or her work to be effective. Robert Brooke and John Hendricks examine the difficult task of teaching ""writing for an audience"" in a classroom where students know that the teacher, not the addressed audience, assigns the grade. The authors describe in detail a particular writing class, taught by Brooke and observed by Hendricks, that attempted to teach writing for an audience. By combining the experiences from their study with student reactions to the class, t